Why grids in accounting? - Terhi Chakhovich; Elton G. McGoun (Elsevier, 2025)
Grids are ubiquitous in the modern world. This paper explores how the concrete spaces of urban grids, some of the earliest forms of grids, parallel the spaces of today's accounting grids. The origins of these urban grids afford profound insights into the preference for grids as employed in contemporary accounting. The reasons for grids are here explored in the framework of the structural properties introduced by Giddens: signification, legitimation, and domination. Grids are shown to signify issues with positive connotations that can also be related to accounting, such as efficiency, quantification, and rationality, as well as transcendental ideals about “correctness”, “justice”, “truth” and “equality”. These significations legitimate grids and their contents and produce domination of the issues gridded. Domination is also achieved by grids signifying and legitimating control and order. Moreover, the prevalence of grids can be explained by their simplicity and their ability to be easily extended; these characteristics assist in the signification of the contents gridded, thereby again legitimating grids themselves as well as their contents and producing domination of the accounting space. Underlying all these factors is the so-called oblique effect according to which humans have an inherent physical preference to see issues around them in gridiron forms.